2019
DOI: 10.1177/1069397119887669
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Variations in Resilience Capacity and Posttraumatic Stress: A Tri-Cultural Comparison

Abstract: Resilience capacity has been associated with individuals’ flexibility and adaptability in responding to potential trauma. Culture-related appraisals influence not only interpretations of etiology of posttraumatic stress disorder (PTSD) and perception of severity of PTSD symptoms but also flexible coping strategies. However, adequate research of the mechanisms on how culture may affect the relationship between resilience and PTSD does not yet exist. The present study focused on whether and how culture (America,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
(43 reference statements)
1
9
0
Order By: Relevance
“…First, participants across the three refugee groups reported that social support offered to one another in the family plays a real difference in their lives and their struggles, and this finding has also been found in previous family resilience studies (Goodman et al, 2017;McCleary, 2017;Zheng et al, 2020). In line with earlier studies on family resilience, our research emphasizes the vital role of family social support in helping refugees cope with the stress associated with postresettlement adjustment.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…First, participants across the three refugee groups reported that social support offered to one another in the family plays a real difference in their lives and their struggles, and this finding has also been found in previous family resilience studies (Goodman et al, 2017;McCleary, 2017;Zheng et al, 2020). In line with earlier studies on family resilience, our research emphasizes the vital role of family social support in helping refugees cope with the stress associated with postresettlement adjustment.…”
Section: Discussionsupporting
confidence: 88%
“…Resilience refers to "the ability to … show positive adaptation in spite of significant life adversities and the ability to adapt to difficult and challenging life experiences" (Sossou et al, 2008, p. 367). The concept of family resilience was developed to draw attention to the role of family resources and strengths at the face of adversarial life experiences, in addition to individual characteristics such as optimism, adaptability, perseverance, control, and hardiness (Gori et al, 2021;Toth, 2003;Zheng et al, 2020). Family resilience highlights how a crisis or ongoing adversity, such as acculturative stress, not only affects individual family members but also impacts the whole family as a unit.…”
Section: The Role Of Family In Refugee Adjustment and Family Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…Hence, these results are reliable to a certain extent but should be used with caution. Second, previous studies indicate that there are specific differences in various cultures when people experience traumatic events (Zheng et al, 2020). Since the current study only explores changes in China, cross-cultural research should be considered in the future.…”
Section: Limitationsmentioning
confidence: 99%
“…Previously, the results of a three-culture (American culture, Chinese culture, and the culture in Hong Kong) analysis on resilience capacity and trauma have indicated that culture significantly moderates the relationship between levels of resilience capacity and severity of PTSD symptoms (Zheng et al, 2019). Specifically, resilience capacity has been found to be a significant predictor of severity of PTSD symptoms in the American sample and in the Mainland China sample, but not in the Hong Kong sample.…”
Section: Trauma Resilience Capacity and Culturementioning
confidence: 99%